ETIKA MORAL DAN INTEGRITAS TERSELENGGARANYA SISTIM DEMOKRASI PEMILIHAN LANGSUNG KEPALA DAERAH 2024 SESUAI NILAI YANG TERKANDUNG DALAM PANCASILA - Sinaga, Maniur (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
Democracy is a main pillar in the Indonesian government system which is based on the 1945 Constitution and adopts a presidential system with direct elections every five years. General Elections (Pileg and Pilpres) and Regional Head Elections (Pilkada) are part of the Pancasila Democracy system which emphasizes ethics and morals in the nation and state. Pilkada as a form of democracy provides constitutional rights for citizens to elect regional leaders who are considered worthy. This direct election strengthens the democratic system with the principles of direct, general, free, and secret (Luber), but faces major challenges, including the potential for disputes in court. This study uses a normative research method with a statutory regulatory approach and case studies on the implementation of democracy in the 2024 Pilkada. The legal basis used includes Law No. 10 of 2016 concerning Pilkada and Law No. 7 of 2017 concerning Elections, which are a follow-up to the Constitutional Court Decision No. 14 of 2013. The results of this study indicate that there is a close relationship between the values ​​of Pancasila and democracy in the 2024 Pilkada, especially in the aspects of justice, equal rights, and political participation based on national ethics and morals. However, the implementation of Pancasila values ​​in the democratic process still faces challenges, such as money politics, hoaxes, and political polarization that can erode the integrity of the election. Therefore, it is necessary to strengthen ethics and morals in the 2024 Pilkada through political education, strict law enforcement, and optimization of the role of election organizers and supervisors.